Psychological capital and happiness at the workplace: The mediating role of flow experience - Charles Kawalya; John C. Munene; Joseph Mpeera Ntayi; James Kagaari; Sam Mafabi; Francis Kasekende (Cogent Business & Management, 2019)
The purpose of this paper is to report on the results of the study to establish the mediating role of flow experience on the relationship between psychological capital and happiness at the workplace with a focus on public hospitals in Uganda. This study was cross-sectional and a total sample size of 800 professional nurses in public hospitals in Uganda was considered. The findings indicated that flow experience partially mediates the relationship between psychological capital and happiness at the workplace. Besides, the finding also indicated that there is a significant and positive relationship between psychological capital and happiness at the workplace. The findings correspond to the argument that in the face of the variety of theoretical and practical implications provided, there is a need for professional workers to be innately involved in their work if their psychological capital is to affect their level of happiness at the workplace. However, this paper is limited by the fact that the respondents' emotions were examined through a cross-sectional research design and the time effects of these emotions were not examined and remain unknown under this study.
Keywords: 650; psychological capital; happiness at work; professional nurses; health services; flow experience; positive emotions